CAPITAL MARKET REACTION TO THE IMPLEMENTATION OF THE 2024 SIMULTANEOUS ELECTION ON THE JAKARTA ISLAMIC INDEX STOCK GROUP - Yuriani, Ima; Lating, Ade Irma Suryani; Muflihin, Mohammad Dliyaul (International Journal of Accounting Innovation, 2025)
Objective: This research is motivated by political phenomena related to the 2024 Simultaneous Elections in Indonesia. This study aims to examine whether the organization of the 2024 Simultaneous Elections provides significant information. A quantitative approach is used by utilizing secondary data, including daily closing prices, JCI index, trading volume, number of shares outstanding, as well as the bid and ask prices of stocks in the Jakarta Islamic Index for seven days before and after the election. Method: Hypothesis testing was conducted using paired sample t-test with Kolmogorov-Smirnov normality test. Results:  The results showed no significant difference in the average stock price, average abnormal return, and average bid-ask spread before and after the election. However, there is a significant difference in the average trading volume activity variable, which indicates the presence of information reflected by these changes. Based on these findings, it can be concluded that the market does not fully respond to election events, as market participants do not seem to consider the information generated as important.  Novelty: This journal examines the combination of several variables found in different studies, as well as hot and crucial phenomena.